Literature and Emotions an Empirical Test through HRV Biofeedback at Taibah University - Yousaf, Iftikhar; Muhammad Nubli, Abdul Wahab; Nor Ashikin, Abdul Aziz; Muhammad, Iqbal (European Centre for Research Training and Development UK, 2016)
motions create literature and literature expresses emotions. Following this proposition, the current study examines the relative effect of “Waiting for Godot” and “Dr. Faustus” towards the peruser’s feelings through HRV biofeedback. The objective of the study is: to determine the comparative impact of “Waiting for Godot” and “Dr. Faustus” towards HRV of the perusers. An aggregate number of 66 members was equally grouped in 3 batches and each member was given the Scripts in Original Text, Paraphrase and Arabic Translation for the maximal cognizance of the messages of the plays and resultantly the optimum excitement of the feelings. Photoplethysmograph Ear Sensor was clung to one of the earlobes of the peruser from one side while its other side was connected to the emWave programme to record the HRV of the peruser. The outcomes exhibit that the two plays influence the feelings of their respective perusers in a different way. The HRV power spectrum demonstrates that the VLF ratio of the perusers of Script 1 rises while LF, HF, Achievement, Coherence and LF/HF Ratio diminish. On the other hand, for Script 2, VLF rate of the perusers diminishes while LF, HF, Achievement, Coherence and LF/HF Ratio rise. From these outcomes, it is unmistakably clear that a piece of literature which talks against the religion of the Muslim perusers makes a negative effect on their feelings and they feel stressed. On the other hand, the writing which passes on the message supporting the religious philosophy of the Muslim perusers positively influences their feelings and they feel relaxed. In general, the consequences of the study demonstrate the concomitant relationship between literature and emotions.